Effect Of Photoperiode On Cell Density And Chlorophyll-a Chlorella sp. Laboratory Scale - Putalan, Reinal; Widiastuti, Irawati Mei (FAPETKAN UNTAD, 2019)
Chlorella sp. as a source of nutrition for aquatic organisms. Chlorella sp. is one way to meet the needs of aquatic organism feed. In the culture of Chlorella sp., light plays an important role in the process of photosynthesis. The photoperiod of the light will affect the density of cells and chlorophyll produced by Chlorella sp. Therefore, it is necessary to analyze cell density and chlorophyll content with different lighting periods. The purpose of this study was to determine cell density and chlorophyll-a content with different light photoperiode in Chlorella sp. culture laboratory scale. This study was used a complete randomized design with 3 treatments (A (12T: 12G), B (16T: 8G), and C (20T: 4G) and 6 replications. The results show that treatment B (16T: 8G) produces the highest cell density ( 1733.5 x 104 cells / ml) while the highest chlorophyll-a content in treatment A (12T: 12G) was 9.76 Î¼g / ml.